Saint Brigid's Bones : a Celtic adventure - Freeman, Philip, 1961- (Pegasus Books, 2014)
"In an evocative Celtic novel set in a time when druids roamed the land, lively young sister Deirdre embarks on a mission to find the stolen bones of her convent's patron saint. In ancient Ireland, an island ruled by kings and druids, the nuns of Saint Brigid are fighting to keep their monastery alive. When the bones of Brigid go missing from their church, the theft threatens to destroy all they have worked for. No one knows the danger they face better than Sister Deirdre, a young nun torn between two worlds. Trained as a bard and raised by a druid grandmother, she must draw upon all of her skills, both as a bard and as a nun, to find the bones before the convent begins to lose faith."--Publisher's website.